What do guidelines and systematic reviews tell us about the management of medically unexplained symptoms in primary care?. Issue 3 (2017) - Hartman, Tim C olde; Rosendal, Marianne; Aamland, Aase; Horst, Henriette E van der; Rosmalen, Judith GM; Burton, Chris D; Lucassen, Peter LBJ
No abstract available